Recent advances in palladium-based electrocatalysts for fuel cell reactions and hydrogen evolution reaction. (November 2016) - Zhang, Lulu; Chang, Qiaowan; Chen, Huimei; Shao, Minhua
Abstract: Platinum (Pt)-based materials are the first choice as the electrocatalyts for many electrochemical reactions including those in fuel cells and electrolyzers due to their excellent activity and stability in harsh environments. Despite its lower cost, palladium (Pd) has attracted much less attention due to relatively lower activity and stability than Pt. Great efforts have been focusing on developing more active and stable Pd-based electrocatalyts aiming to partially or completely replace costly Pt for the past decade. This paper overviews the recent advances in Pd-based electrocatalysts for hydrogen evolution reaction (HER), and fuel cell reactions including hydrogen oxidation reaction (HOR), oxygen reduction reaction (ORR), ethanol oxidation reaction (EOR) and formic acid oxidation reaction (FAOR). Graphical abstract: Palladium-based materials are promising to partially or completely replace platinum in many electrocatalytic reactions. The recent advances in development of more active palladium-based electrocatalysts toward hydrogen evolution, hydrogen oxidation, oxygen reduction, ethanol oxidation, and formic acid oxidation reactions are reviewed. Highlights: Recent progress in Pd electrocatalysis is summarized. Anodic reactions including hydrogen, ethanol and formic acid oxidation reactions are reviewed. Cathodic reactions including hydrogen evolution and oxygen reduction reactions are reviewed. Pd alloys, surface modifications, support and structural effects are highlighted.